Study of Soil Development and Classification on the South Slope of Mount Pucung, Bumiaji Kodya Batu District - Fahmi Habib; Abdul Mukri Prabowo; M. Luthfi Rayes (Central Research Institute For Agriculture, 2022)
The main objective of this research are: To study influence of slope position and slope level and also landuse system to the soil development that coming from volcanic ash materials of Mount Pucung and To study level of soil development in southern slope of Pucung Mountain. While the hypothesis is: Difference of slope position, slope level and heighth result to the existence of difference of soil development 2) Difference of landuse have an effect on reality to the soil development. This research is hired at Pucung Mountain toposekuen which consist of 4 observation soils profile at various solpe position that is P1 (Volcanic plain, flat-wavy, Lower Slope), P2 (Footslope, surging, Middle Slope), P3 (Foot Slope, hilly, Upper Slope) and P4 (Volcanic plain, flat, Top). This research through some step that is 1) survey preliminary phase 2) field survey phase which soil profile description, interview and take of soil sample 3) soil physics and soil chemistry laboratory analysis, and 4) Soil cassification phase come up with category of sub-grup pursuant to Soil Taxonomy USDA year 1999. Observation parameter are soil morphology that is forming of horison, colour, structure, to analyse the nature of physical that is texture, Bulk Density, Soil aggregate stability while soil chemistry pparameters is organic materials content, Base Saturation, CEC, percentage of Al ½ Fe, Soil Acidity and retention of P used as indicator of soil development. Result of from this research are 1) Level of soil development in southern slope of Pucung mountain influenced by topographic position, degree and also landuse management 2) Topography and difference of landuse management cause the differences of soil development of morphology, chemistry and physical soil characteristic so that cause change to arranging the name of soil classification and 3) Soil development at P1 and P2 with landuse of apple garden in lower and middle slope, classified as Aquic Eutrudepts and Andic Eutrudepts while at P3 classified as Typic Hapludands and for the P4 (Top) classified as Typic Melanudands.